2021
DOI: 10.1128/spectrum.00295-21
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the RNA Exosome Complex and RNA-Binding Protein Ssd1 in Maintaining Cell Wall Stability in Yeast

Abstract: Stressful conditions such as high temperatures can compromise cellular integrity and cause bursting. In microorganisms surrounded by a cell wall, such as yeast, the cell wall is the primary shield that protects cells from environmental stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Comparison of Ssd1-associated mRNAs identified by CRAC analysis [46] with previous RIP and transcriptome data [47][48][49] showed that 11 mRNAs were systematically bound by Ssd1 (Table 1). Among these 11 mRNAs, 8 were also highly enriched by eIF2A, including CTS1, SUN4 and SRL1 (Fig 1 , Table 1, S5 Table and S1 Dataset).…”
Section: Eif2a Requires the Presence Of Ssd1 To Associate With Severa...mentioning
confidence: 69%
See 2 more Smart Citations
“…Comparison of Ssd1-associated mRNAs identified by CRAC analysis [46] with previous RIP and transcriptome data [47][48][49] showed that 11 mRNAs were systematically bound by Ssd1 (Table 1). Among these 11 mRNAs, 8 were also highly enriched by eIF2A, including CTS1, SUN4 and SRL1 (Fig 1 , Table 1, S5 Table and S1 Dataset).…”
Section: Eif2a Requires the Presence Of Ssd1 To Associate With Severa...mentioning
confidence: 69%
“…Interestingly, we observed a robust enrichment of Ssd1 (Fig 5B). Ssd1 is a RNA-binding protein (RBP) and previous studies have reported that Ssd1 binds to about a hundred mRNA coding for proteins involved in cell wall biogenesis [46][47][48][49]. Ssd1 directly recognizes a consensus motif usually located in the 5' UTR of these mRNA targets [46].…”
Section: The Rna Binding Protein Ssd1 Is Highly Enriched By Eif2a Ind...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that under the heat shock condition, the macro morphology and micro morphology of the strain were changed to some extent. Yeast cell wall is the basic structure that determines cell shape and protects cells from environmental in uences, and heat stress can adversely affect the integrity of cell wall and cell membrane [33,34]-[. The cell membrane has selective transmitability, which can control the entry and exit of substances into and out of cells, and the components of cells such as nucleic acids will not be lost to the outside of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of its strains show a well-established probiotic effect [21]. Being well-studied and easy to genetically modify [22][23][24], S. cerevisiae is also readily chosen as a workhorse in modern bioprocesses aimed at the biosynthesis of biofuels, recombinant proteins, and biologically active small molecules [25], such as caffeine, resveratrol, morphine, and artemisinin [26]. Finally, it serves as a chassis for many eukaryotic whole-cell biosensors [27].…”
Section: Introductionmentioning
confidence: 99%